2021
DOI: 10.1002/ejic.202100664
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanism of Amorphization for Co‐URJC‐5

Abstract: Irreversible transition from monocrystalline to amorphous phase accompanied by a change in coordination geometry (octahedral to tetrahedral) was first observed in a Co(II)‐based MOF material, named Co‐URJC‐5, via SO2 uptake. This structural change is associated with the total loss of the pyridine ligand from the axial positions. These results are corroborated using PXRD and FT‐IR spectroscopy. A plausible amorphization mechanism is proposed using crystal field theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…37 It was calculated in the range of −43.7−51.5 kJ mol −1 (Figure S6), which corresponds to a strong physisorption process and whereby the strong capture at low pressures of SO 2 is justified. This value is comparable with other MOFs with a similar surface area, for example, Co-URJC-5 22 and UNAM-1. 36 Clearly, the adsorption and desorption branches coincide, excluding a possible hysteresis and confirming an SO 2 physisorption process.…”
Section: Characterization Of Muf-16supporting
confidence: 85%
See 3 more Smart Citations
“…37 It was calculated in the range of −43.7−51.5 kJ mol −1 (Figure S6), which corresponds to a strong physisorption process and whereby the strong capture at low pressures of SO 2 is justified. This value is comparable with other MOFs with a similar surface area, for example, Co-URJC-5 22 and UNAM-1. 36 Clearly, the adsorption and desorption branches coincide, excluding a possible hysteresis and confirming an SO 2 physisorption process.…”
Section: Characterization Of Muf-16supporting
confidence: 85%
“…Additionally, the N 2 adsorption isotherm was measured (Figure S9), and the BET surface area was estimated, resulting in 217 m 2 g –1 , and by using SEM images, an average particle size of 3.06 μm (Figure S10) was determined with ImageJ software, which shows that neither the porosity nor the morphology of the material is affected by harsh conditions such as SO 2 in the presence of water vapor. The above contrasts with MOFs made of Co, as for example, the material Co-URJC-5, in which when exposed to SO 2 , the Co­(II) metal center changes in its coordination sphere from octahedral to tetrahedral, destroying the crystal structure of the material. Furthermore, it is shown that the hydrogen bonds forming the structure of MUF-16 are robust enough to prevent Co­(II) from undergoing changes in its coordination sphere.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…23 At a low pressure from 0 to 0.05 bar, the MOP-CDC achieves an SO 2 capture of 1.0 mmol g −1 . This result is comparable to some representative MOF materials with a considerable surface area such as NU-1000 (1.2 mmol g −1 ), 24 Co-URJC-5 (0.8 mmol g −1 ), 25 and Zn(bdc) (ted) 0.5 (1.2 mmol g −1 ), 26 among others (see Table S1 †). The maximum SO 2 uptake capacity at 1 bar is approximately 2.0 mmol g −1 .…”
supporting
confidence: 81%